Prepubertal Development of Gonadotropin-Releasing Hormone Neuron Activity Is Altered by Sex, Age, and Prenatal Androgen Exposure - Dulka, Eden A. (Endocrinology, 2017)
Gonadotropin-releasing hormone (GnRH) neurons regulate reproduction though pulsatile hormone release. Disruption of GnRH release as measured via luteinizing hormone (LH) pulses occurs in polycystic ovary syndrome (PCOS), and in young hyperandrogenemic girls. In adult prenatally androgenized (PNA) mice, which exhibit many aspects of PCOS, increased LH is associated with increased GnRH neuron action potential firing. How GnRH neuron activity develops over the prepubertal period and whether this is altered by sex or prenatal androgen treatment are unknown. We hypothesized GnRH neurons are active before puberty and that this activity is sexually differentiated and altered by PNA. Dams were injected with dihydrotestosterone (DHT) on days 16 to 18 post copulation to generate PNA mice. Action potential firing of GFP-identified GnRH neurons in brain slices from 1-, 2-, 3-, and 4-week-old and adult mice was monitored. GnRH neurons were active at all ages tested. In control females, activity increased with age through 3 weeks, then decreased to adult levels. In contrast, activity did not change in PNA females and was reduced at 3 weeks. Activity was higher in control females than males from 2 to 3 weeks. PNA did not affect GnRH neuron firing rate in males at any age. Short-term action potential patterns were also affected by age and PNA treatment. GnRH neurons are thus typically more active during the prepubertal period than adulthood, and PNA reduces prepubertal activity in females. Prepubertal activity may play a role in establishing sexually differentiated neuronal networks upstream of GnRH neurons; androgen-induced changes during this time may contribute to the adult PNA, and possibly PCOS, phenotype.